Uwarunkowania meteorologiczne silnych burz - analiza przypadku z 10 lipca 2020 roku - Stępczyński, Dawid (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2023)
Considered the most dangerous type of thunderstorm, supercell thunderstorms appear in strictly defined meteorological conditions in the troposphere. Predicting their location is particularly problematic in an environment of strong vertical wind shear and low instability. An example of such a situation is the supercell that contributed to the development of the tornado on July 10, 2020 at 18:10 CEST in Ustronie Morskie. On that day, two dangerous supercells were also created, which, at the peak of activity, passed over Lubusz and Masovian Provinces. The tornado in Ustronie Morskie was formed on the wavy front, while the supercell developing in Lubusz and Mazovia Land was observed on the cold front. Large hail and damaging wind gusts associated with the downburst in the west of the country took place in higher atmospheric instability than the other cases. The MLCAPE was over 200 J kg–1 higher than that for peak activity of the other storms discussed in the paper. This could have been crucial for the formation of the largest hail recorded on July 10, 2020 in Poland. The highest values of wind shear and storm relative helicity occurred on the coast which could have influenced the formation of a tornado despite the low values of atmospheric instability. The hook echo radar signature in Mazovia Land developed with a similar MLCAPE as the tornado on the coast (nearly 500 J kg–1). On the other hand, the MUCAPE and SBCAPE was much higher there (approx. 500 J kg–1 more), and so was the LCL level. This proves a higher humidity deficit in the lower troposphere in the place where the hook echo passes. With regard to the ESTOFEX and Skywarn Polska convection outlook, the tornado was the most difficult phenomenon to predict. Hail and damaging wind gusts not related to rotation coincided to a greater extent with the convective outlook.